Assessment of Aggressiveness of Breast Cancer Using Simultaneous 18F-FDG-PET and DCE-MRI: Preliminary Observation. (August 2016) - Margolis, Nathaniel E.; Moy, Linda; Sigmund, Eric E.; Freed, Melanie; McKellop, Jason; Melsaether, Amy N.; Kim, Sungheon Gene
Abstract : Purpose: This study aims to investigate the feasibility of using simultaneous breast MRI and PET to assess the synergy of MR pharmacokinetic and fluorine-18 fluorodeoxyglucose ( 18 F-FDG) uptake data to characterize tumor aggressiveness in terms of metastatic burden and Ki67 status. Methods: Twelve consecutive patients underwent breast and whole-body PET/MRI. During the MR scan, PET events were simultaneously accumulated. MR contrast kinetic model parametric maps were computed using the extended Tofts model, including the volume transfer constant between blood plasma and the interstitial space (K trans ), the transfer constant from the interstitial space to the blood plasma (kep ), and the plasmatic volume fraction (Vp ). Results: Patients with systemic metastases had a significantly lower kep compared to those with local disease (0.45 vs. 0.99 min −1, P = 0.011). Metastatic burden correlated positively with K trans and standardized uptake value (SUV), and negatively with kep . Ki67 positive tumors had a significantly greater K trans compared to Ki67 negative tumors (0.29 vs. 0.45 min −1, P = 0.03). A negative correlation was found between metabolic tumor volume and transfer constant (K trans or Kep ). Conclusion: These preliminary results suggest that MR pharmacokinetic parameters and FDG-PET may aid in the assessment of tumor aggressiveness and metastatic potential. Future studies are warranted with a larger cohort to further assess the role of pharmacokinetic modeling in simultaneous PET/MRI imaging.